Room‐temperature X‐ray response of cadmium–zinc–telluride pixel detectors grown by the vertical Bridgman technique. (27th January 2020) - Abbene, Leonardo; Principato, Fabio; Gerardi, Gaetano; Buttacavoli, Antonino; Cascio, Donato; Bettelli, Manuele; Amadè, Nicola Sarzi; Seller, Paul; Veale, Matthew C.; Fox, Oliver; Sawhney, Kawal; Zanettini, Silvia; et al.
Abstract : Sub‐millimetre arrays with pixel pitch less than 500 mm, based on boron oxide encapsulated vertical Bridgman grown cadmium–zinc–telluride crystals, were fabricated. Excellent room‐temperature performance characterizes the detectors even at high‐bias‐voltage operation (9000 V cm −1 ) with energy resolution of 1 keV FWHM at 60 keV. Abstract : In this work, the spectroscopic performances of new cadmium–zinc–telluride (CZT) pixel detectors recently developed at IMEM‐CNR of Parma (Italy) are presented. Sub‐millimetre arrays with pixel pitch less than 500 µm, based on boron oxide encapsulated vertical Bridgman grown CZT crystals, were fabricated. Excellent room‐temperature performance characterizes the detectors even at high‐bias‐voltage operation (9000 V cm −1 ), with energy resolutions (FWHM) of 4% (0.9 keV), 1.7% (1 keV) and 1.3% (1.6 keV) at 22.1, 59.5 and 122.1 keV, respectively. Charge‐sharing investigations were performed with both uncollimated and collimated synchrotron X‐ray beams with particular attention to the mitigation of the charge losses at the inter‐pixel gap region. High‐rate measurements demonstrated the absence of high‐flux radiation‐induced polarization phenomena up to 2 × 10 6  photons mm −2  s −1 . These activities are in the framework of an international collaboration on the development of energy‐resolved photon‐counting systems for high‐flux energy‐resolved X‐ray imaging.